2012
DOI: 10.1152/ajpgi.00389.2011
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in patients with cirrhosis and portal hypertension

Abstract: Erice E, Llop E, Berzigotti A, Abraldes JG, Conget I, Seijo S, Reverter E, Albillos A, Bosch J, García-Pagán JC. Insulin resistance in patients with cirrhosis and portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…The relationship between HOMA-2 index and portal hypertension was reported previously in a cohort of cirrhotic patients with mixed etiology [18] and it was shown that the HOMA index significantly predicts the presence of esophageal varices in CHC-related cirrhotic patients irrespective of the presence of diabetes [19]. The pathophysiological link between portal hypertension and IR could be potentially explained by the fact that insulin can modulate the endothelial synthesis of nitric oxide and endothelin [28,29], to induce tumor necrosis factor alpha secretion, and to stimulate hepatic stellate cells [19,30,31].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The relationship between HOMA-2 index and portal hypertension was reported previously in a cohort of cirrhotic patients with mixed etiology [18] and it was shown that the HOMA index significantly predicts the presence of esophageal varices in CHC-related cirrhotic patients irrespective of the presence of diabetes [19]. The pathophysiological link between portal hypertension and IR could be potentially explained by the fact that insulin can modulate the endothelial synthesis of nitric oxide and endothelin [28,29], to induce tumor necrosis factor alpha secretion, and to stimulate hepatic stellate cells [19,30,31].…”
Section: Discussionsupporting
confidence: 67%
“…Eighty percent of the patients had alcohol consumption more than 80 g/day. The median MELD score was 15 [9][10][11][12][13][14][15][16][17][18][19][20][21] and 26% of the patients had compensated (Child-Pugh score A) cirrhosis. The median HOMA-2 index value was 2 (1.2-3.1) in our population of ALD cirrhotic patients.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In tissue from human liver diseases associated with hepatic insulin resistance (eg NAFLD, ALD and NASH (14)) and elevated VAP-1 expression, we have demonstrated modifications in GLUT expression compared to normal livers (Fig 2). Human studies have linked insulin resistance to altered expression of GLUT isoforms by granulosa cells (28)and adipose tissue (33) and rodent livers demonstrate increased GLUT-1 and decreased GLUT-2 expression when insulin resistance is induced by high fat diet (54) or alcohol exposure (48).…”
Section: Discussionmentioning
confidence: 78%
“…23 No 4: 397-403 reduced insulin clearance secondary to hepatic insu ciency and porto-systemic shunting [10]. It was also demonstrated that insulin resistance is positively correlated with portal hypertension (PHT) evaluated directly by hepatic venous pressure gradient (HVPG) measurement [11] or indirectly as the presence of esophageal varices (EV) [12]. Furthermore, obesity and diabetes represent independent risk factors for development of hepatocellular carcinoma in patients with NASH [13].…”
Section: Introductionmentioning
confidence: 99%